LEGO Harry Potter : building the magical world - Dowsett, Elizabeth (New York : DK Pub., 2011)
Gives readers an up-close look at the bricks, constructions, and minifigures of the LEGO® Harry Potter universe -- from Hogwarts Castle to Hagrid's hut.
Includes index.
"With exclusive minifigure!"--Cover.
Keywords: Potter, Harry -- (Fictitious character) -- Juvenile literature; Potter, Harry -- (Fictitious character); Models and modelmaking -- Juvenile literature; LEGO toys -- Juvenile literature; Harry Potter films -- Juvenile literature; Models and modelmaking; LEGO toys; Harry Potter films; LEGO toys; Models and modelmaking; Harry Potter films